Mengagas Pengelolaan Penilaian untuk Peningkatan Pembelajaran - Taufiqurrahman Taufiqurrahman (Program Pascasarjana Universitas Ibrahimy, 2016)
Assessment and instructional are interrelated. Assessment’s role depends on instructional approach. An instruction putting students as subject of their own learning will posit assessment as basis for instructional improvement. Otherwise, assessment will be applied to judge student learning outcomes. The first assessment’s role will work if only teachers master the quality assessment and do it collaboratively. At school level, work procedures include data summarizing, problem solving, modelling and externalization. The use of assessment data is method for improving an instructinal system incrementally.